Implementasi Challenge-Based Learning dalam Pembelajaran Piano Tingkat Lanjut di FKIP Untan: Sebuah Kajian Analitis - Zakarias Aria Widyatama Putra Aria (Program Studi Pendidikan Musik FBS UNP, 2023)
Purpose: This study aims to analyze the Advanced Basic Piano learning model with a Challenge-Based Learning (CBL) approach as a solution to problems in developing learning models and optimizing students' piano playing skills in the Performing Arts Education Study Program, FKIP, Tanjungpura University (Untan). Against the background of the need for understanding the impact of CBL learning models on learning outcomes, especially in piano practice, this study focuses on the initial overview of previous learning models, CBL implementation processes, and analysis of learning outcomes. Method: Using qualitative methods with case studies, data were collected through observation, unstructured interviews, and documentation. Data analysis involves data reduction, data presentation, and inference, with data validity checked through assignment values, UTS, UAS, and source triangulation. Result and Discussion: The results showed that the CBL learning model had a positive effect on piano learning outcomes, measured by 21 students achieving final grades in the good category. In conclusion, the CBL learning model can optimally improve students' piano learning outcomes, and recommendations are given to piano educators and tutors to adopt this model in lecture practice.